(untitled) (Acta Scientiarum. Biological Sciences, 2021)
Inselbergs are granitic or gneissic rocky outcrops prevalent in the landscape of southeastern Brazil. These ecosystems represent islands of isolated habitats that harbor a peculiar flora with high richness and endemism. The present study lists the species of vascular plants occurring in the Pedra da Andorinha Complex, located in the municipality of Jerônimo Monteiro/Cachoeiro de Itapemirim, southern Espírito Santo state, aiming to generate subsidies for the creation of a protected area. The survey was performed between July 2017 and October 2018, resulting in a record of 121 species, 96 genera, and 40 families. Bromeliaceae (17), Orchidaceae (12) and Fabaceae (10) were the richest families. The phytophysiognomy of exposed rock vegetation comprises a greater number of species (79 species) compared to the woody rupicolous communities (42). Eighteen of the collected species are threatened by extinction; a new species was discovered; and five were described based on materials previously collected in the studied location — Alcantarea patriae, Anthurium martinellii, Coleocephalocereus uebelmanniorum, Stigmatodon attenuatoides and Pitcairnia azouryi, the first four being endemic to the region. We also found Tabebuia reticulata, a rare species among Brazilian flora. Our results highlight the biological importance of the Pedra das Andorinhas Complex and reinforce the need to create a protected area to preserve biodiversity and the regional natural heritage.